Abusing ETFs. (5th August 2016) - Bhattacharya, Utpal; Loos, Benjamin; Meyer, Steffen; Hackethal, Andreas
Abstract: Using data from a large German brokerage, we find that individuals investing in passive exchange-traded funds (ETFs) do not improve their portfolio performance, even before transaction costs. Further analysis suggests that this is because of poor ETF timing as well as poor ETF selection (relative to the choice of low-cost, well-diversified ETFs). An exploration of investor heterogeneity shows that though investors who trade more have worse ETF timing, no groups of investors benefit by using ETFs, and no groups will lose by investing in low-cost, well-diversified ETFs.